Preclinical evaluation of invariant natural killer T cells in the 5T33 multiple myeloma model. - Haneen Nur (Public Library of Science (PLoS), 2013)
Immunomodulators have been used in recent years to reactivate host anti-tumor immunity in several hematological malignancies. This report describes the effect of activating natural killer T (NKT) cells by α-Galactosylceramide (α-GalCer) in the 5T33MM model of multiple myeloma (MM). NKT cells are T lymphocytes, co-expressing T and NK receptors, while invariant NKT cells (iNKTs) also express a unique semi-invariant TCR α-chain. We followed iNKT numbers during the development of the disease in both 5T33MM mice and MM patients and found that their numbers dropped dramatically at the end stage of the disease, leading to a loss of total IFN-γ secretion. We furthermore observed that α-GalCer treatment significantly increased the survival of 5T33MM diseased mice. Taken together, our data demonstrate for the first time the possibility of using a preclinical murine MM model to study the effects of α-GalCer and show promising results of α-GalCer treatment in a low tumor burden setting.